Do Female Managers Help to Lower Within-Firm Gender Pay Gaps? Public Institutions vs. Private Enterprises - Iga Magda; Ewa Cukrowska-Torzewska (Institute of Labor Economics (IZA), 2018)
We analyze the link between the presence of female managers and the size of the firm-level gender pay gap, looking separately at the private and public sector. Using a large linked employer-employee dataset for Poland and a non-parametric and parametric decompositions, we find that higher presence of female managers is associated with more pay advantage towards women in selected types of public sector units: the ones in which remunerations of women and men are already equal, and a large share of the workforce is tertiary-educated. The effects are, however, relatively small in size. In private establishments, lower gender wage inequality is associated with higher shares of female workers, but not female managers.
Keywords: J16; J31; J45; 330; gender wage gap; wage inequalities; public sector; female managers; \~Nopo decomposition; Oaxaca- Blinder decomposition